Effect of Fiber Orientation on Tensile Properties of Short Glass Fiber Reinforced Injection Molding Polypropylene Composite - Ya'acob, Abdul Malek (2004)
The objective of this study is to examine the behaviour of composites and to provide an overview of short glass fiber reinforced injection-moulded theimoplastic, SgFRIMT in relation to the fiber orientation direction. In this study, the relationship between the mechanical propesties of samples containing longitudinal and transverse direction was studied in terms of the effects of injection speed, fiber concentration and fiber length on the mechanical properties of SgFRIMT. The orientation of fiber distribution in longitudinal and transverse direction was measured according to the gate position and samples- taken from identified position were investigated and tested at an angle relative to the fiber direction. The composite consisting of 5, 10, 15% wt of glass fiber was prepared using single screw extsuder model Brabender Plasticoder PL 2000, a compression molding machine and an 80-tonne Toshiba injection molding machine. The tensile properties were evaluated by Instron testing machine model 4301. The discussion focuses on the effects of fiber concentration, injecting speed and fiber length on tensile properties of a SgFRIMT. Tensile strength shows a steady decrease with increasing percentage of fiber loadings. In contrast, the tensile modulus increases significantly with an increase in the fiber loadings. At higher fiber concentration, the values of the modulus were higher than those of the unfilled polypropylene. The fiber breakage that occurs during sample preparation reduces the overall tensile strength significantly. Additional investigation was carried out on the effect of fiber breakage using 6 and 12 mm fiber length, where it was obsesved that the fiber breakage occurs during compounding stages with approximately 80% reduction in initial fiber length. Observation on the extrudates reveals that poor fiber matrix interaction causes the failure of the prepared samples. The presence of void and the agglomeration inside the samples considerably affects the mechanical properties of the composites. The results indicate that the stiffness and toughness of the SgFRIMT generally are influenced by the addition of glass fibers. In this study the influence of the injection speed was insignificant. The results of average fiber length agree with the results of other previous studies on SgFRIMT materials, indicating that the fiber length has major influence on the tensile properties of the prepased samples.